27. ASSOCIATION BETWEEN THE PRESENCE OF ESTROGEN RECEPTOR ON SKIN LESIONS AND SUBCLINICAL CHARACTERISTICS OF PATIENTS SYSTEMIC LUPUS ERYTHEMATOUS (Vietnam Journal of Community Medicine, 2024)
Objective: To investigate the association between the presence of estrogen receptor α (ERα) on the skin lesions and subclinical characteristics of patients with systemic lupus erythematosus (SLE). Subjects and methods: This is a case seriers of 65 female patients diagnosed with systemic lupus erythematosus at the National Dermatology Hospital from January 2022 to August 2023. Serum autoantibodies were examined in all 65 patients. Histopathological examination and immunohistochemical staining was conducted among 36 of 65 patients to detect the presence of ERα in the skin lesions. Results: The positive rate of Anti Smith was 23.1%; anti Ro/SSA was 30% and anti LA/SSB was 7%. ERα was positive in 38.9% of cases and negative in 61.1% of cases. There was no association between the presence of ERα receptor on skin lesions and histopathology characteristics as well as serum autoantibodies of SLE patients. Conclusion: The presence of ERα in skin lesions was detected in 38.9% of SLE cases. No association was found between the presence of ERα in skin lesions subclinical characteristics of SLE patients.
Keywords: Estrogen receptor α, systemic lupus erythematosus, subclinical characteristics.